Многозондовое подключающее устройство для контроля BGA-компонентов - Невлюдов, И. Ш.; Палагин, В. А.; Тымчук, И. Т.; Разумов-Фризюк, Е. А.; Жарикова, И. В. (ХНУРЭ, 2010)
The given work is devoted to the modern developments in the field of microelectromechanical checking up devices in the manufacturing of radio-electronic apparatus. In particular BGA-components for surface mounting are considered and checking up device for such components is described. Developed multiprobes connecting device provide high reliability and accuracy of control process and reduce cost of devices and testing operation time considerably.
Keywords: BGA; микроэлектромеханическое многозондовое подключающее устройство (МПУ); электронные компоненты; многозондовое подключающее устройство